Parenting Orientations as Antecedents of Children's Violent Videogame Play. Issue 2 (30th September 2015) - Walker, Doug; Laczniak, Russell N.; Carlson, Les; Brocato, E. Deanne
Abstract : The study investigates caregiver influence on children's playing of violent videogames. Based on theory, the investigation develops and tests a model that links parental socialization tendencies to children's violent videogame play. Results from a national sample of 237 caregiver–child dyads suggest that while the primary caregivers' tendencies toward warmth and restrictiveness likely lessen children's play levels of violent videogames, their predispositions toward anxious emotional involvement tend to increase play. Moreover, results suggest that these relationships are mediated by caregiver mediation of videogames.